Pengaruh Faktor Internal dan Eksternal Perusahaan Terhadap Audit Report Lag (Arl) pada Perusahaan BUMN yang Tercatat di Bursa Efek Indonesia - Sigit Handoyo; Dwiayu Fatmasari (Jurnal Aplikasi Bisnis, 2017)
This research aims to test the influence of internal and external factors of the company towards audit report lag (ARL). Variables measured in this study are the net profits, solvency, size of the company, the reputation, the auditor's opinion, and the audit fee. The study was done by using a purposive sampling method by taking the company's annual report on STATE-OWNED ENTERPRISES (BUMN) listed on the Indonesia Stock Exchange. Total company met the criteria as samples were 14 companies during the years 2009 to 2011. In this research, hypothesis testing was using multiple regression analysis. The results of this research show that the variable net profits, solvency, the size of the company and the auditor's reputation do not have a significant influence toward the audit report lag, where as the variable auditor's opinions and audit fee have a significant influence toward the audit report lag.